Real world evidence of dupilumab effectiveness in a Colombian cohort of patients diagnosed with severe asthma - Alí-Munive, Abraham; Zakzuk, Josefina; Alvis-Zakzuk, Nelson J.; García, Elizabeth; Diaz Bossa, Claudia; Cano Rosales, Diana Jimena; Bolívar, Fabio; Carreño, Alejandro; Rodríguez-Ordoñez, Paula; Gómez-Ardila, Natalia; Patiño, Gabriel; Londoño, Sergio; et al. (Frontiers in Allergy, 2025)
BackgroundReal-world effectiveness and safety of dupilumab for asthma treatment have been evaluated in USA and Europe, but research from Latin America is lacking. We aimed to describe the effectiveness of dupilumab in terms of changes in the annual rate of asthma exacerbations (AER) and their impact on lung function in Colombian patients.MethodsReal-world, descriptive, and multi-centric (five clinical centers located in four different cities in Colombia) retrospective study that included patients aged ≥18 years with severe asthma, as defined by the GINA criteria. Data were collected from medical records of medical centers specialized in pulmonology or allergy care) spanning from 12 months before the prescription of dupilumab (baseline) to 25 months later. Follow-up data were categorized at various time points (2–4, 5–7, 8–10, 11–13, 14–18, and 19–25 months). Main outcomes were annual rates of asthma exacerbations (emergency visits or hospitalizations due to asthma), lung function measured through FEV1 and percent predicted FEV1 (FEV1pp), and Asthma Control Test (ACT) scores. Outcome rates were compared between baseline and follow-up data points. FeNO and absolute eosinophil counts throughout the observed period was also explored.ResultsA total of 98 patients were included. At baseline, the mean AER was 0.61 ± 1.45 per adult. Lower AER were observed after one (0.11 ± 0.54) or two-years (0.08 ± 0.20) of dupilumab treatment (p = 0.03). FEV1 measurements after one or two years of dupilumab treatment were significantly lower than baseline (p = 0.03). Mean change from baseline in FEV1 was 302.1 ± 481.97 ml (n = 19), 282.00 ± 231.99 ml (n = 10), and 248.18 ± 281.21 ml (n = 11) in the 2–4-, 11–13-, and 19–25-month follow-up periods, respectively. FEV1pp showed higher but not significant values from the 2–4-month period, with a median change of 12.5% (IQR: 0.3, 21.5). The proportion of patients with uncontrolled asthma (ACT ≤15) decreased from 68% at baseline to 19% and 20% at year-one and second year of treatment, respectively (p = 0.003). The proportion of patients reaching FeNO values below 25 ppb was lower after dupilumab treatment than in baseline (p < 0.0001). Of the total cohort (n = 99), 15 (15.2%) experienced an adverse event (AE). Three patients discontinued dupilumab permanently, and two discontinued dupilumab due to AEs.ConclusionsDupilumab is an effective and well-tolerated treatment for severe asthma in Colombia, resulting in reduced exacerbations and improved asthma control, lung function, and FeNO levels.